2020
DOI: 10.1038/s41598-020-72050-2
|View full text |Cite
|
Sign up to set email alerts
|

Koala immunogenetics and chlamydial strain type are more directly involved in chlamydial disease progression in koalas from two south east Queensland koala populations than koala retrovirus subtypes

Abstract: Chlamydial disease control is increasingly utilised as a management tool to stabilise declining koala populations, and yet we have a limited understanding of the factors that contribute to disease progression. To examine the impact of host and pathogen genetics, we selected two geographically separated south east Queensland koala populations, differentially affected by chlamydial disease, and analysed koala major histocompatibility complex (MHC) genes, circulating strains of Chlamydia pecorum and koala retrovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…The detection of C. psittaci in a wallaby joint in this study is the first detection of C. psittaci in a marsupial. However, the severe impact of C. pecorum infections on Australian koalas, resulting in reproductive, urinary, and ocular disease, is well known [ 8 , 29 ]. Earlier reports of C. psittaci in koalas have since been revised, and to date, there remains no evidence of C. psittaci in koalas, nor any other marsupial.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of C. psittaci in a wallaby joint in this study is the first detection of C. psittaci in a marsupial. However, the severe impact of C. pecorum infections on Australian koalas, resulting in reproductive, urinary, and ocular disease, is well known [ 8 , 29 ]. Earlier reports of C. psittaci in koalas have since been revised, and to date, there remains no evidence of C. psittaci in koalas, nor any other marsupial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has determined that KoRV proviral profiles generated from multiple sample types can be combined for analysis (12), so all samples were DNA extracted, PCR amplified to obtain the KoRV envelope gene receptor binding region from all subtypes simultaneously, deep amplicon sequenced and processed to obtain representative operational taxonomic units (OTUs) or strains present in each koala. This procedure is on February 1, 2021 by guest http://jvi.asm.org/ Downloaded from analogous to several previous KoRV proviral studies (7,11,12,19,20). Study samples generated an average of 188,016 ± 69,301 KoRV proviral reads, with an overall average Good's coverage estimate of 0.999996, meaning that overall, each sample was predicted to have been profiled to 99.9996% completion.…”
Section: Resultsmentioning
confidence: 95%
“…Studies investigating the allelic diversity of class II subunits within DA and DB genes have found that the beta subfamilies (DAB and DBB) contain more allelic diversity than the alpha subfamilies (DAA and DAA), leading to more focus on the beta subfamilies in research studies [ 45 ]. As such, the current collection of sequenced koala MHC class II alleles stands at three DAA, 42 DAB, three DBA, 26 DBB, three DCB, and four DMB alleles, with DCA and DMA alleles yet to be characterised [ 43 , 47 , 48 ].…”
Section: Chlamydial Infection Disease and Vaccine Responses In Kmentioning
confidence: 99%
“…In the same population, koalas possessing the DBB*04 allele had higher levels of Chlamydia heat shock protein 60 (c-hsp60) antibody levels than koalas without DBB*04 [ 47 ]. Moving further north to examine koalas already infected with Chlamydia in southeast Queensland, Australia, DAB*10 and DBB*04 alleles again emerged with significant associations, but to different circumstances [ 48 ]. In these infected koalas, both DAB*10 and UC*01:01 alleles were significantly more prevalent in infected koalas that did not progress to clinical disease, while DBB*04 and DCB*03 alleles were significantly more prevalent in infected koalas that did progress to clinical disease [ 48 ].…”
Section: Chlamydial Infection Disease and Vaccine Responses In Kmentioning
confidence: 99%
See 1 more Smart Citation